Paternalizm w prawie i etyce zawodowej - Łabieniec, Paweł (Filozofia Publiczna i Edukacja Demokratyczna, 2013)
The concept of the paternalism is known since the end of the 19th century. The paternalistic attitude has been criticized not only by liberals. According to this criticism the essence of evil of paternalism lies in the negation of the autonomy of persons who are the subject of paternalistic activities. However some forms of paternalism are considered as acceptable not only in legal regulations but also on the ground of the legal ethics. The text shows in what a way ethics of legal professions in the USA and Poland protects the autonomy of clients and under what conditions lets lawyers to act paternalistically.